2009
DOI: 10.1007/s12088-009-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morphine on Mycobacterium smegmatis infection in mice and macrophages

Abstract: The immunomodulatory effects of opioids are known in various infections. However, little is known about the effects of opioids in tuberculosis (TB). In the present study, we report the effects of morphine in Mycobacterium smegmatis infection in mice and macrophages. Morphine exerted a dose-dependent suppression of infection in vivo: 50 and 100 mg/kg morphine exerted signifi cant (P<0.05) suppression whereas 5 mg/kg morphine showed no effect. Analogous to the in vivo effects, incubation of M. smegmatis -infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A possible explanation is that opioids affect the immune response directly; in vitro and animal studies have found deleterious effects of opioids in infections [ 20 ]. In relation to mycobacteria specifically, studies show mixed results; some finding advantageous effects of opioids [ 32 ], others showing deleterious effects [ 33 , 34 ]. In addition, we have previously shown biological effects of heroin use on the expression of chemokines and chemokine receptors among HIV-infected individuals [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that opioids affect the immune response directly; in vitro and animal studies have found deleterious effects of opioids in infections [ 20 ]. In relation to mycobacteria specifically, studies show mixed results; some finding advantageous effects of opioids [ 32 ], others showing deleterious effects [ 33 , 34 ]. In addition, we have previously shown biological effects of heroin use on the expression of chemokines and chemokine receptors among HIV-infected individuals [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed for bacterial counts in PBS containing 0.05% Tween 80 (59). The number of cfu per 1 ϫ 10 6 cells was determined by plating 10-fold serial dilutions of cell lysates on Middlebrook 7H10 plates complemented with 0.5% glycerol and 10% oleic albumin dextrose complex enrichment (59,60). For selective medium, 40 g/ml kanamycin was added.…”
Section: Assessment Of Intracellular Bacterial Cfumentioning
confidence: 99%